A great country : a novel - Gowda, Shilpi Somaya (Mariner Books, 2024)
"Pacific Hills, California: Gated communities, ocean views, well-tended lawns, serene pools, and now the new home of the Shah family. For the Shah parents, who came to America twenty years earlier with little more than an education and their new marriage, this move represents the culmination of years of hard work and dreaming. For their children, born and raised in America, success is not so simple. For the most part, these differences among the five members of the Shah family are minor irritants, arguments between parents and children, older and younger siblings. But one Saturday night, the twelve-year-old son is arrested. The fallout from that event will shake each family member's perception of themselves as individuals, as community members, as Americans, and will lead each to consider: how do we define success? At what cost comes ambition? And what is our role and responsibility in the cultural mosaic of modern America?"--